The Enantiomer of Allopregnanolone Prevents Pressure-Mediated Retinal Degeneration Via Autophagy - Ishikawa, Makoto; Nakazawa, Toru; Kunikata, Hiroshi; Sato, Kota; Yoshitomi, Takeshi; Krishnan, Kathiresan; Covey, Douglas F.; Zorumski, Charles F.; Izumi, Yukitoshi (Frontiers in Pharmacology, 2022)
In an ex vivo rat ocular hypertension (OHT) model, the neurosteroid allopregnanolone (AlloP) exerts neuroprotective effects via enhancement of both GABAA receptors and autophagy. We now examine whether its enantiomer (ent-AlloP), which is largely inactive at GABA receptors, offers similar neuroprotection in ex vivo and in vivo rat OHT models. Ex vivo rat retinal preparations were incubated in a hyperbaric condition (10 and 75 mmHg) for 24 hours. An in vivo ocular hypertension (OHT) model was induced by intracameral injection of polystyrene microbeads. We examined pharmacological effects of AlloP, ent-AlloP, picrotoxin (a GABAA receptor antagonist), and 3-MA （an autophagy inhibitor）, histologically and biochemically. We found that both AlloP and ent-AlloP have marked neuroprotective effects in the retina, but effects of the unnatural enantiomer are independent of GABAA receptors. Electron microscopic analyses show that pressure elevation significantly increased autophagosomes (APs) in the nerve fiber layer and addition of AlloP also increased APs and degenerative autophagic vacuoles (AVds). ent-AlloP markedly increased APs and AVds compared to AlloP. Examination of LC3B-II and SQSTM1 protein levels using immunoblotting revealed that AlloP increased LC3B-II, and ent-AlloP further enhanced LC3B-II and suppressed SQSTM1, indicating that autophagy is a major mechanism underlying neuroprotection by ent-AlloP. In an rat in vivo OHT model, single intravitreal ent-AlloP injection prevented apoptotic cell death of retinal ganglion cells similar to AlloP. However, even in this model, ent-AlloP was more effective in activating autophagy than AlloP. We conclude that ent-AlloP may be a prototype of potential therapeutic for treatment of glaucoma as an autophagy enhancer without affecting GABA receptors.